Decision Model for Best Contraceptive Technique Recommendation Based on Patient's Ideal Profile - Hugo, Veronika Novia; Sudipa, I Gede Iwan; Libraeni, Luh Gede Bevi; Pratistha, Indra; Atmaja, Ketut Jaya (Politeknik Ganesha Medan, 2026)
Choosing the right contraceptive method is essential to support the success of family planning programs. Many patients still choose methods without considering their medical conditions, which can lead to failure or side effects. This study designed a decision-making model based on Profile Matching to recommend contraceptive methods according to the patient’s ideal profile. The dataset was obtained from Faskes Level 1 Udayana Denpasar. Validation was conducted through discussions with midwives as experts, referring to the KLOP KB Wheel as the standard issued by the WHO. The evaluation results show a high level of agreement between the model’s recommendations and expert judgments, indicating that the model provides more objective and easily understood recommendations compared to manual approaches.